Overexpression of thioredoxin in islets transduced by a lentiviral vector prolongs graft survival in autoimmune diabetic NOD mice - Chou, Feng-Cheng (BioMed Central, 2009)
ABSTRACT: Pancreatic islet transplantation is considered an appropriate treatment to achieve insulin independence in type I diabetic patients. However, islet isolation and transplantation-induced oxidative stress and autoimmune-mediated destruction are still the major obstacles to the long-term survival of graft islets in this potential therapy. To protect islet grafts from inflammatory damage and prolong their survival, we transduced islets with an antioxidative gene thioredoxin (TRX) using a lentiviral vector before transplantation. We hypothesized that the overexpression of TRX in islets would prolong islet graft survival when transplanted into diabetic non-obese diabetic (NOD) mice. METHODS: Islets were isolated from NOD mice and transduced with lentivirus carrying TRX (Lt-TRX) or enhanced green fluorescence protein (Lt-eGFP), respectively. Transduced islets were transplanted under the left kidney capsule of female diabetic NOD mice, and blood glucose concentration was monitored daily after transplantation. The histology of the islet graft was assessed at the end of the study. The protective effect of TRX on islets was investigated. RESULTS: The lentiviral vector effectively transduced islets without altering the glucose-stimulating insulin-secretory function of islets. Overexpression of TRX in islets reduced hydrogen peroxide-induced cytotoxicity in vitro. After transplantation into diabetic NOD mice, euglycemia was maintained for significantly longer in Lt-TRX-transduced islets than in Lt-eGFP-transduced islets; the mean graft survival was 18 vs. 6.5 days (n = 9 and 10, respectively, p < 0.05). CONCLUSION: We successfully transduced the TRX gene into islets and demonstrated that these genetically modified grafts are resistant to inflammatory insult and survived longer in diabetic recipients. Our results further support the concept that the reactive oxygen species (ROS) scavenger and antiapoptotic functions of TRX are critical to islet survival after transplantation.